Perbandingan Scholl Well Being Muhammadiyah Boarding School di Kota dan Desa Pekalongan - Setyawan, M. Adin Setyawan (Program Studi Psikologi Islam, 2022)
The school situation is very important to note. Schools with good school situations can bring up maximum learning outcomes, while negative school situations can cause learning experiences that lead to negative emotions such as stress, depression, and suicide. Islamic boarding schools need to assess whether the environmental situation is positive or negative. Assessment of the pesantren situation by students can be carried out using the School Well Being (SWB) approach. Muhammadiyah Boarding School (MBS) is a boarding school in the Muhammadiyah environment which is spread both in villages and cities. This study wants to see an overview of SBM SWB in cities and villages, also wants to find out whether there are differences in SBM SWB in cities and villages. The method used is the mix method, using a quantitative and qualitative approach. The result is the second SWB of MBS in the good category. There is no difference in SWB between the two urban and rural MBS. The qualitative results can be read further in this journal.